Technology Blueprint HT Sdn Bhd / Nur Alisa Natrah Abdul Karim - Abdul Karim, Nur Alisa Natrah (2020)
HTSdnBhd is a start-up private company that starts its operation in Johor since 1 January 2018. It is a partnership company and focusing on selling an existing and innovation product which are electric jug kettle, bread toaster and 2 in 1 heater in the market. 2 in 1 heater is an innovation product that has a combination of two product functions into one product. It is an affordable, multifunction and easy-handle product.